Pengaruh Penambahan H2SO4 dan Perubahan Temperatur pada Nitrasi Metil Risinoleat - Abdullah, Abdullah; K, Meilina H; Mustikasari, Kamilia (ALCHEMY, 2017)
NNitration on methyl ricinoleate can produce an additive for improving the cetane number of diesel oil. This article describes the effect of the addition of the H2SO4 and temperature variations on the concentration of nitration products. Nitration process on methyl ricinoleate was carried out by using a mixture of nitric acid, acetic anhydride and sulfuric acid. Based on GC analysis, it can be concluded that the nitration of methyl ricinoleate with an increasing amount of H2SO4 tend to reduce concentration of the product, while the increasing of temperature tend to the opposite. Nitration of methyl ricinoleate with addition of H2SO42.5% at 50Â°C was the optimum conditions in this study, where the concentrations of products was 23.74%. FTIR analysis showed that the product contained the new compound with nitrate group as a product of nitration.